Minocycline rescues decrease in neurogenesis, increase in microglia cytokines and deficits in sensorimotor gating in an animal model of schizophrenia - Mattei, Daniele; Djodari-Irani, Anaïs; Hadar, Ravit; Pelz, Andreas; de Cossío, Lourdes Fernandez; Goetz, Thomas; Matyash, Marina; Kettenmann, Helmut; Winter, Christine; Wolf, Susanne A. (Brain, behavior, and immunity, 2014)
Adult neurogenesis in the hippocampus is impaired in schizophrenic patients and in an animal model of schizophrenia. Amongst a plethora of regulators, the immune system has been shown repeatedly to strongly modulate neurogenesis under physiological and pathological conditions. It is well accepted, that schizophrenic patients have an aberrant peripheral immune status, which is also reflected in the animal model. The microglia as the intrinsic immune competent cells of the brain have recently come into focus as possible therapeutic targets in schizophrenia. We here used a maternal immune stimulation rodent model of schizophrenia in which polyinosinic–polycytidilic acid (Poly I:C) was injected into pregnant rats to mimic an anti-viral immune response. We identified microglia IL-1β and TNF-α increase constituting the factors correlating best with decreases in net-neurogenesis and impairment in pre-pulse inhibition of a startle response in the Poly I:C model. Treatment with the antibiotic minocycline (3mg/kg/day) normalized microglial cytokine production in the hippocampus and rescued neurogenesis and behavior. We could also show that enhanced microglial TNF-α and IL-1β production in the hippocampus was accompanied by a decrease in the pro-proliferative TNFR2 receptor expression on neuronal progenitor cells, which could be attenuated by minocycline. These findings strongly support the idea to use anti-inflammatory drugs to target microglia activation as an adjunctive therapy in schizophrenic patients.